Hydrogen peroxide disrupts the regulatory pathway of saliva secretion in two salivary acinar rat cell lines - Golnarnik, Golnaz; Søland, Tine M.; Galtung, Hilde K.; Haug, Trude M. (Frontiers in Molecular Biosciences, 2024)
BackgroundSecretion of saliva is controlled by autonomic nerve signals via regulation of Ca2+-dependent ion transport across acinar cell membranes. Oxidative stress may affect this process, leading to a decrease in saliva production. This study investigates elements of the Ca2+ regulatory pathway and their vulnerability to hydrogen peroxide-induced oxidative stress.MethodsRat parotid and submandibular salivary gland acinar cell lines were exposed to different hydrogen peroxide concentrations to simulate oxidative stress. Cell viability and intracellular reactive oxygen species were measured, mRNA levels were assessed via RT-qPCR, and protein expression was studied using western blot and immunofluorescence microscopy.ResultsElevated concentrations of hydrogen peroxide reduced cell viability and increased intracellular levels of reactive oxygen species and led to a decrease in cholinergic receptor muscarinic 3 and adrenoreceptor alpha 1A mRNA and protein levels in both cell lines. In parotid gland cells, both mRNA and protein levels of stromal interaction molecule 1 and Orai1 decreased with increasing concentrations of hydrogen peroxide. In contrast, in submandibular gland cells stromal interaction molecule 1 and Orai1 displayed differential mRNA and protein expression levels.ConclusionOur study revealed that hydrogen peroxide exposure alters rat parotid and submandibular acinar cells, increasing reactive oxygen species and reducing autonomic receptor expression. Differential mRNA and protein expression of stromal interaction molecule 1 and Orai1 highlight complex oxidative stress effects on Ca2⁺ signaling. Most likely these effects will be deleterious to salivary secretion, but some effects may be protective.